2023
DOI: 10.21203/rs.3.rs-3179604/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Demonstration of a Terahertz Coplanar-Strip Spoof-Surface-Plasmon Polariton Low Pass Filter

Abstract: There is a growing interest in Spoof Surface Plasmon Polariton (SSPP) structures at Terahertz (THz) frequencies for applications such as filtering, sensing, and communications. However, to date, there are limited experiments which confirm SSPP characteristics at THz frequencies. The majority of literature focuses on simulation or verification by device scaling down to Gigahertz (GHz) frequencies where standard vector network analyzers are readily available. This paper presents the first experimental verificati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The bandwidths are significantly higher in [35][36][37], about 100 GHz. In addition, bandwidths of 300 GHz and 250 GHz are observed in [22,23]; however, design 7 of this study, as shown in Table 2, far exceeds them (∼400 GHz).…”
Section: Performance Summary and Comparisonmentioning
confidence: 52%
See 2 more Smart Citations
“…The bandwidths are significantly higher in [35][36][37], about 100 GHz. In addition, bandwidths of 300 GHz and 250 GHz are observed in [22,23]; however, design 7 of this study, as shown in Table 2, far exceeds them (∼400 GHz).…”
Section: Performance Summary and Comparisonmentioning
confidence: 52%
“…Compact SSPP transmission lines have been designed that do not use the conventional gradient transition for SSPP excitation [22]. Another recent advancement involves the experimental verification of SSPP behaviour beyond 1 THz [23]. Three structures with band-edge frequencies of 0.53 THz, 0.63 THz and 1.04 THz have been designed and transmission characteristics were verified using a terahertz-time-domain spectrometer system.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation